The Implementation of Prophetic Values to Maintain Journalist Professionalism - Emeraldien, Fikry Zahria; Sugihartati, Rahma; Iqbal, Dwiki; Annisa, Qhoirun; Ardelia, Putri (Proceedings of International Conference on Da'wa and Communication, 2021)
Campus journalism is a place for students to develop their potential in the journalism field. Students who are agents of change not only provide quality news but also provide moral value in the news production process. Quality news can be raised through the role of a journalist in writing news (information). Prophetic journalism is a journalistic concept taken from the nature of the prophets. In this paper, we examine the application of the concept of prophetic journalism –journalism that imitates the prophetic characteristics of the Prophet Muhammad– among campus journalists. Prophet Muhammad is known for his four characteristics: siddiq (delivering accurate information), amanah (trustworthy as a source of information), tabligh (delivering information in its entirety), fathanah (a journalist is required to be smart in revealing the truth of the news). The data from this study is the result of observations from the daily life of the researcher when carrying out the news production process with other campus journalists ranging from electronic media (radio & television), print, and online. The results of this study indicate that campus journalists at UIN Sunan Ampel Surabaya apply prophetic journalism well. By implementing the prophetic characteristics of the Prophet Muhammad when carrying out journalistic activities, journalists can maintain the professionalism of journalists. By using ethnographic research methods or commonly referred to as field research, researchers make observations as the main data and are equipped with in-depth interviews with several campus journalists. We also propose the nature of Prophet Ibrahim to be incorporated into the concept of prophetic journalism as well. Prophet Ibrahim is known for the story of his courage to seek the truth and reveal it when everyone was against it. This courage is important in supporting journalistic activities among students and professionals.